EVALUATION OF CARDIAC BIOMARKERS IN THE PERICARDIAL FLUID TO DETECT DEATH DUE TO ISCHAEMIC HEART DISEASE - AN AUTOPSY BASED STUDY - M, Venkatesan; Vedant,; S, Sneha; Chand, Leena; Pradhan, Priyadarshee (Journal of Forensic Medicine and Toxicology, 2025)
Death is not an event; it is a process. 10% of all deaths are sudden and unexpected deaths. 45% to 50% of sudden deaths involve the cardiovascular system. Heart diseases are one of the most common causes of sudden death. The body of the deceased is brought for autopsy in cases of sudden death to ascertain the cause of death. the identification of early myocardial infarcts at autopsy poses a challenge to the autopsy surgeon, since unequivocal gross changes of infarcts do not become evident for the first twenty-four to forty-eight hours following the ischemic injury to myocardium. Clinicians use cardiac biomarkers such as CPK, CPK-MB, Troponin I&T, to screen living patients for acute MI. Hence if these markers could be measured from the pericardial fluid and if found to be high in cases of sudden death due to myocardial ischemia, they could prove a vital clue to establish the cause of death. Pericardial fluid is easy to collect, analyze and gives accurate results even, a long time after death. The aim of this study hence is to detect varying levels of cardiac biomarkers CPK and CPK-MB in the pericardial fluid to confirm myocardial infarction or ischemic heart disease as the cause for sudden death. Pericardial fluid was collected in 50 cases of sudden death and the levels of biomarkers measured. Levels of both markers were elevated. However further studies are required to evaluate the applicability of these markers to detect sudden death cases due to cardiac causes.
Keywords: Sudden Death; Cardiovascular system; ischemic heart disease; Bio markers; Creatine phosphokinase